Arthroscopic-Assisted Treatment of a Reversed Hill-Sachs Lesion: Description of a New Technique Using Cerament - S. Bark; F. Renken; A. P. Schulz; A. Paech; J. Gille (Case Reports in Orthopedics)
Purpose. Impaction fractures of the anterior aspect of the humeral head, the reversed Hill-Sachs lesion, are common in posterior shoulder dislocation. We present a new technique to address these lesions arthroscopic-assisted with the use of a bone substitute. Methods. We report the case of a 45-year-old male with a reversed Hill-Sachs lesion after posterior shoulder dislocation. Initially a glenohumeral arthroscopy is performed to address concomitant intra-articular injuries. Guided by the k-wire a cannulated sizer was inserted for reduction of the fracture under arthroscopic visualization. For reduction of the impacted part of the humeral head the subcortical defect was filled with an injectable bone substitute (Cerament) to prevent secondary dislocation. Results. X-ray at follow-up 6 months after the index procedure documents the bony remodeling of the bone substitute. At that time the patient was pain-free (VAS 0) and satisfied with the outcome (Constant score: 78, Rand-36 score: 84, Rowe score: 81) with a good ROM. Conclusions. In conclusion, arthroscopic-assisted reconstruction of reversed Hill-Sachs lesions with an injectable bone substitute is feasible and may provide patients with all the benefits of an anatomic reconstruction with decreased risks related to open surgery.